الفصيح والأفصح في العربيّة - Abdullah Khalaf AL.Waeli, Nahla (Journal of College of Education, 2022)
This research sheds light on (the eloquent and the most eloquent) in Arabic, which is limited to identify the main reasons rather than mentioning many examples. The research introduces the linguistic origin of eloquence, the home of eloquence, and from those who took the first linguists, indicating the priority of the Arabic language over all other languages. The researcher, then, mentions the most important reasons for this phenomenon by focusing on what descended in the Holy Qur’an - even if it is not on their Arab linguists’ analogy. This is because the verbal in the Holy Qur’an, i.e., the worshiper book by reciting it, is widely used in the lives of Muslims, especially in their various devotional duties. Finally, the researcher summarizes the most important elements and topics that were mentioned in the research.